Family Resource Management Patterns in the Context of Children in Conflict with the law in Nodal Areas - Clara, Evy; Syaifudin, Syaifudin; Adiani, Rosita (IJBLE Scientific Publications Community Inc., 2025)
This study aims to analyze the forms and characteristics of family resource management patterns in the context of children in conflict with the law (CCL) in nodal areas, as well as to examine the factors influencing their effectiveness in the child’s recovery and social reintegration processes. Employing a qualitative approach within the family sociology paradigm and Bronfenbrenner’s social ecology theory, the research was conducted in densely populated urban nodal regions such as East Jakarta and North Jakarta. Data were collected through in-depth interviews with 15 families of CCL, correctional officers (BAPAS), social workers, and community leaders, supported by field observations and documentation. The findings reveal three major family resource management patterns: (1) reactive-survival, characterized by short-term efforts focused on meeting basic needs; (2) adaptive-restructuring, reflecting the family’s ability to reorganize roles and social resources; and (3) participatory-restorative, emphasizing collaboration with communities and institutions in the child’s recovery process. The effectiveness of family resource management is influenced by six main factors: economic conditions, family structure, communication patterns, social support, the quality of the nodal environment, and public policy. The study concludes that family resource management functions as an adaptive and protective social mechanism determining the success of child recovery and family resilience amid the structural pressures of nodal urban areas.